Level of Public Trust in Alms in Modern Times - Godzali, Galva Al; Wisnu Ikhwansyah Saputra; Rafif Isdarufa Athallah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Alms is a right that a person gives to another person voluntarily, both in physical and non-physical form. In Islam itself, almsgiving has certainly become the highest icon of worship because there is a lot of goodness in it, this has been explained a lot in the Koran and Hadith. Indonesia itself is a country where the majority are Muslim, so almsgiving itself has become part of worship apart from obligatory worship. Digital almsgiving usually uses certain methods that provoke prosocial motivation in most people. This also makes people prefer to give some of their wealth to people who are good at attracting this motivation rather than to people who need it. This was once expressed by one YouTuber who said that he could reap abundant profits just by doing live streaming and the YouTuber also considered this to be support from fans